B-cells and non-B-cells immunoglobulins expression in canine perianal gland tumours: a preliminary study - Rifici, Claudia; Lusi, Elena Angela; Giambrone, Giada; Ieni, Antonio; Napoli, Ettore; Mannarino, Cornelia; Zappone, Viola; Mazzullo, Giuseppe (Frontiers in Veterinary Science, 2025)
Although the focus in tumor immunology has been on T cells, B cells may play a crucial role in modulating tumor responses. Among products released in the tumour microenvironment, Immunoglobulins (Igs) have been associated with the development and progression of various types of human cancer. However, their role in veterinary oncology has yet to be fully investigated. It has long been widely acknowledged that Igs are produced solely by B-lineage cells. However, several studies have shown that Ig is also expressed by many normal and pathological “non-B” cells, including neoplastic cells. The aim of this study was to investigate the role of B-cells and Igs in tumours of the canine hepatoglands. Immunohistochemical analysis of ten hepatoid adenomas, thirteen well-differentiated hepatoid carcinomas and nine undifferentiated hepatoid carcinomas revealed that adenomatous structures exhibit the greatest concentration of CD79a-positive, IgA-producing B cells. In contrast, in malignant tumours, an inverse association was observed between CD79a expression and the presence of IgG, accompanied by a significant increase in tumour antigen-specific IgG. These results suggest that IgG produced by neoplastic cells could contribute to tumour progression behavior, potentially serving as prognostic biomarkers and therapeutic targets.